2018
DOI: 10.1051/e3sconf/20182801003
|View full text |Cite
|
Sign up to set email alerts
|

Re-entrained road dust PM10 emission from selected streets of Krakow and its impact on air quality

Abstract: Abstract. Scientific research studies conducted in various parts of the world confirm that PM10 concentrations in urban air depend to a great extent on the resuspension processes of the dust deposited on the road surface. The paper presents the results of the study related to the determination of the re-entrained PM10 emissions from four selected streets of Krakow (Southern Poland) together with the assessment of its impact on air quality. Examined streets are characterised by different traffic intensity (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…In a study by Patra et al (2008), the determined transfer into the atmosphere of the PM10 fraction of road dust was 40%. Similar values were found in a study by Bogacki et al (2018). Additionally, re-suspension of road dust is significantly reduced in the low-traffic area because of the low-traffic density.…”
Section: Composition Of Road Dust Size Fractionssupporting
confidence: 89%
See 1 more Smart Citation
“…In a study by Patra et al (2008), the determined transfer into the atmosphere of the PM10 fraction of road dust was 40%. Similar values were found in a study by Bogacki et al (2018). Additionally, re-suspension of road dust is significantly reduced in the low-traffic area because of the low-traffic density.…”
Section: Composition Of Road Dust Size Fractionssupporting
confidence: 89%
“…Traffic-related particulate matter (PM) emissions originate from vehicle tailpipe exhausts as well as from wear of brake pads and discs, tires and the road surface (Loganathan et al 2013). A recent study performed in Krakow (Bogacki et al 2018) demonstrated the importance of the reentrained road dust on PM10, which can be responsible for up to 25% of the total PM10 concentration near the roads during winter and even up to 50% in summer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many other studies present long-term trends in changes of air pollutants concentrations in Krakow and their impact on health [74][75][76][77][78][79][80][81][82], the mineralogical composition and microbiological characteristics of aerosols [83,84], the oxidative potential of PM 10 and PM 2.5 [85], the chemical composition of street dust [86] and dry and wet deposition [87][88][89]. The results of measurements from the automatic air quality monitoring station in Krakow were also used to prepare the pollution background necessary in the process of air pollution modeling and the assessment or validation of the dispersion [90][91][92][93][94][95][96][97] or prognostic [98][99][100][101] models used.…”
Section: Introductionmentioning
confidence: 99%
“…A dozen or so years ago, the combustion of solid fuels (mainly coal) in small furnaces and boilers (related to residential heating) and industrial energy production had the dominant contribution to the high levels of PM 10 in the air in the winter months [72,73]. Thanks to the large-scale elimination of stoves and boilers fired with solid fuels carried out in recent years and replacing them with more ecological energy sources and reducing the emission of pollutants into the air from local industrial plants, emissions from road transport have started to play an increasingly important role for the air pollution in Krakow with regard to fine dust (including engine emission of soot), as well as dust drifted by wind from the road surface and during construction works in dry periods [63,84,[94][95][96].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works concerning traffic-related air pollutants modeling in street canyons were most often aimed at presenting the impact on air quality of the emissions from selected streets usually located near the air quality monitoring stations. In most cases the CALINE4 [39,40] or OSPM [34,35,[41][42][43] was used in these studies.…”
Section: Introductionmentioning
confidence: 99%